How is informed consent related to emotions and empathy? An exploratory neuroethical investigation. Issue 5 (10th March 2011) - Supady, Alexander; Voelkel, Antonie; Witzel, Joachim; Gubka, Udo; Northoff, Georg
Abstract : Context: Informed consent is crucial in daily clinical practice and research in medicine and psychiatry. A recent neuroethical investigation explored the psychological factors that are crucial in determining whether or not subjects give consent. While cognitive functions have been shown to play a central role, the impact of empathy and emotions on subjects' decisions in informed consent remains unclear. Objective: To evaluate the impact of empathy and emotions on subjects' decision in informed consent in an exploratory study. Design: Decisional capacity and informed consent to a subsequent imaging study were evaluated with the MacArthur Competence Assessment Tool for Clinical Research (MacCAT-CR). Empathy and emotion recognition were measured with the Multifaceted Empathy Test (MET) and the Florida Affect Battery (FAB). Setting: Psychiatric subjects were recruited from a general psychiatric hospital and a forensic state hospital. Patients: A mixed group of 98 healthy men and forensic and non-forensic psychiatric subjects were investigated. Results: Both empathy (MET) and emotion recognition (FAB) correlated with MacCAT-CR scores. Higher cognitive empathy and good emotion recognition (compared with low empathy and emotion recognition) were associated with increased decisional capacity and higher rates of refusal to give informed consent. Conclusions: This study shows an empirical relationship between decision-making and informed consent, on the one hand, and emotions and empathy on the other. While this study is exploratory and preliminary, the findings of a relationship between informed consent, emotions and empathy raise important neuroethical questions with regard to an emotional-social concept of informed consent and potential clinical implications for testing informed consent.